2023
DOI: 10.1002/aic.18053
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic volatile organic compounds absorption with phenyl‐based deep eutectic solvents: A molecular thermodynamics and dynamics study

Abstract: The suitability of phenyl‐based deep eutectic solvents (DESs) as absorbents for toluene absorption was investigated by means of thermodynamic modeling and molecular dynamics (MD). The thermodynamic models perturbed‐chain statistical associating fluid theory (PC‐SAFT) and conductor‐like screening model for real solvents (COSMO‐RS) were used to predict the vapor–liquid equilibrium of DES–toluene systems. PC‐SAFT yielded quantitative results even without using any binary fitting parameters. Among the five DESs st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Currently, diverse thermodynamic models comprising UNIQUAC Functional-group Activity Coefficients (UNIFAC), 30 UNIversal QUAsi Chemical (UNIQUAC), 31 and Non-Random Two-Liquid (NRTL), 32 in conjunction with an equation of state techniques like Peng–Robinson state equation (PR-EoS), 33 Cubic-Plus Association (CPA), 34 soft-SAFT, 35 and perturbed chain statistical associating fluid theory (PC-SAFT), 36 have been effectively employed to estimated gas solubility in systems including DESs. These thermodynamic models offer valuable tools for estimating gas solubility in DES-containing systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, diverse thermodynamic models comprising UNIQUAC Functional-group Activity Coefficients (UNIFAC), 30 UNIversal QUAsi Chemical (UNIQUAC), 31 and Non-Random Two-Liquid (NRTL), 32 in conjunction with an equation of state techniques like Peng–Robinson state equation (PR-EoS), 33 Cubic-Plus Association (CPA), 34 soft-SAFT, 35 and perturbed chain statistical associating fluid theory (PC-SAFT), 36 have been effectively employed to estimated gas solubility in systems including DESs. These thermodynamic models offer valuable tools for estimating gas solubility in DES-containing systems.…”
Section: Introductionmentioning
confidence: 99%
“…The development of dependable computational models for predicting CO 2 solubilities in DESs stands as an increasing and highly coveted area of research, as these models expedite the discovery and optimization of DES-based solvent systems, propelling the development of efficient and sustainable solutions for CO 2 emissions mitigation. [27][28][29] Currently, diverse thermodynamic models comprising UNI-QUAC Functional-group Activity Coefficients (UNIFAC), 30 UNIversal QUAsi Chemical (UNIQUAC), 31 and Non-Random Two-Liquid (NRTL), 32 in conjunction with an equation of state techniques like Peng-Robinson state equation (PR-EoS), 33 Cubic-Plus Association (CPA), 34 so-SAFT, 35 and perturbed chain statistical associating uid theory (PC-SAFT), 36 have been effectively employed to estimated gas solubility in systems including DESs. These thermodynamic models offer valuable tools for estimating gas solubility in DES-containing systems.…”
Section: Introductionmentioning
confidence: 99%
“…This method could be used to verify the separation capacity of DESs and provide a strategy for screening a suitable DES as a separating agent for a given mixed system. Yu et al 208 first extended the PC-SAFT model to predict the VLE of toluene−DES systems, demonstrating that the PC-SAFT model could yield quantitative results with a total ARD of only 12.29% without using binary fitting parameters, compared with the COSMO-RS model's total ARD of 24.12%. The findings indicated that the PC-SAFT model can be used as a quantitative thermodynamic model to screen absorbents, predict VLE, and guide process simulation for capturing aromatic volatile organic compounds with DESs.…”
Section: Saft-based Modelsmentioning
confidence: 99%
“…For instance, Cheng and Qi. conducted a comprehensive analysis of the implementation of DESs in stubborn liquid–liquid systems, while Yu et al assessed the potential of DESs to absorb aromatic volatile organic compounds. , Hence, the employment of quaternary ammonium salt DES over traditional methods to capture TCA and CBE in industrial waste gas can be advantageous and circumvent the drawbacks of conventional techniques.…”
Section: Introductionmentioning
confidence: 99%